Qualitative Evaluation of Surface Water Resources Using Iran Water Quality Index (IRWQSC) and National Sanitation Foundation Water Quality Index (Case Study: Kardeh Dam, Mashhad, Iran) - Mohammad Mahdi Shahsavar; Mahdi Najafzadeh; Mehran Akrami; Zahra Kian; Mohammad Gheibi (Annals of Environmental Science and Toxicology - Peertechz Publications, 2021)
The quality of water resources is one of the main subjects in ensuring public health. Therefore, monitoring water resources, especially surface waters, is one of the leading water operational management systems' requirements. Since the quality of surface waters is affected by natural factors and pollutants from human activity, monitoring water resources' quality leads to collecting and extracting valuable data, which needs a suitable method for interpretation and analysis. Therefore, this research assessing the annual quality of Kardeh Dam (One of the surface water sources of Mashhad) based on IRWQISC and NSFWQI qualitative index. The results showed that the Kardeh Dam quality index in spring, summer, autumn, and winter is 55.43, 49.25, 57.61, and 60.9, respectively, indicating relatively good, average, relatively good, and relatively good quality conditions, respectively. Also, according to NSFWQI analysis, the quality index was calculated for spring, summer, autumn, and winter, respectively equal to 86.4 (good), 81.28 (good), 84.48 (good), and 96.64 (excellent). Comparisons showed that IRWQISC was more rigorous than NSFWQI in judging the water quality of the Kardeh Dam. Comparisons indicate that the dam's water quality judgment with the IRWQISC model is far more stringent than the NSFWQI model.